Pendampingan Pencatatan Laporan Keuangan UMKM: Menuju Bisnis Mandiri dan Berdaya Saing - Tirzah Febiola Chandra; Irene Citrawati Khonrad; Alexander Nissan Leksono; Lazaro Batigol Lauwono; Mariana Ing Malelak (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Recording financial statements is a crucial aspect of managing finances for any business to maintain overall financial health. However, business owners face numerous challenges in financial management, particularly Micro, Small, and Medium Enterprises (MSMEs). MSMEs are essential pillars of the Indonesian economy. Nevertheless, many MSMEs still encounter difficulties in financial management, especially in preparing financial statements. This can hinder their growth and competitiveness. Community service activities in assisting financial statement recording are expected to aid Food and Beverage MSMEs in Surabaya to improve its financial management practices. The community service method employed is participatory and educational. The results of this activity have proven to have a positive impact on Food and Beverage MSME. With effective mentoring on financial statements, MSMEs can enhance their self-reliance and competitiveness, thus making a greater contribution to the national economy. Furthermore, MSMEs can strengthen their position in the market and optimize their business growth potential.